Evaluacion del cultivo de Arveja chaucha (pisium sativum) previa a la incorporacion de abono verde de Avena (avena sativa) con tres enmiendas quimicas en terrazas de banco en el sector Salache, parroquia Eloy Alfaro, cantòn Latacunga, provincia de Cotopaxi 2021-2022. - Llamusunta Guasgua, Shirley Edith (2022)
The purpose of this research work was to evaluate the cultivation of pea chaucha (Pisium sativum) prior to the incorporation of oat green manure (Avena sativa) with three chemical amendments in bench terraces at the Technical University of Cotopaxi Salache sector (CEYPSA), an experimental design of completely randomized blocks (DBCA) in a factorial arrangement of 3X3+1 with 3 replications was carried out. The results of the research show that for the germination percentage, ammonium sulfate with a dose of 400kg/Ha obtained an average of 60.83%. In height, the best treatment was ammonium sulfate with a dose of 400kg/Ha, obtaining an average of 70.97% after 90 days. In plant diameter, ammonium sulfate with a dose of 400kg/Ha obtained an average of 1.56% at 90 days. In the number of flowers, the ammonium sulfate treatment with a dose of 400kg/Ha obtained an average of 3.53%. In the number of pods, the ammonium sulfate treatment with a dose of 400kg/Ha obtained 21.27%. In pod length, the ammonium sulfate treatment with a dose of 400kg/Ha obtained 7.78%. In number of peas per pod, ammonium sulfate with a dose of 400 kg/ha obtained 115.23% and in weight of harvested peas, ammonium sulfate with a dose of 400 kg/ha had a better result with 2.74%. At the beginning the percentage of nitrogen was 41%, phosphorus 47.6% and potassium 3.25%, at the end nitrogen decreased to 5.64%, phosphorus decreased to 42.3% and potassium increased to 4.09%, the percentage of organic matter decreased from 1.9% at the beginning to 0.3% at the end, the pH changed from 9.71 at the beginning to 9.64 at the end of the trial. In the comparative analysis of the treatments in the research project, T4 (ammonium sulfate 400 kg/ha) obtained the highest cost-benefit ratio, that is, for each dollar invested, a cost-benefit of 0.36 was recovered. And the one with the lowest profitability was T10 (control), i.e. for each dollar invested no significant benefit is obtained, the cost benefit of this treatment is 0.025, being the lowest value in the table. Due to the above results, the conclusion is that the application of ammonium sulfate is very good for improving the eroded soils of CEASA.